2007
DOI: 10.1590/s1413-70542007000200011
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting colonization and abundance of Aphis gossypii glover (hemiptera: aphididae) on okra plantations

Abstract: The control of Aphis gossypii Glover (Hemiptera: Aphididae) on okra Abelmoschus esculentus (L.) (Malvaceae) consist primarily in the use of insecticides, due to the lack of information on other mortality factors. The objective of this study was to determine the effects of predators and parasitoids, height of canopy, plant age, leaf areas, organic compounds leaves, levels of leaf nitrogen and potassium, density of leaf trichomes, total rainfall and median temperature on attack intensity of A. gossypii on two su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
(39 reference statements)
1
11
0
1
Order By: Relevance
“…However, the effi ciency of botanic products on insects might vary with UV radiation, temperature, and solvent used, or with the concentration of the extract (Moreira et al, 2007). The genetics of the plant, the extraction time of the compounds (Sidhu et al, 2004), leaf areas, organic compounds of leaves, density of leaf trichomes (Leite et al, 2007), and the part of the plant used for producing the extracts further infl uence the activity of some compounds against insects (Siskos et al, 2007). In addition this product is more effi cient in the fi eld, since it activates substances of the secondary metabolism of the plants and thus improving resistance (Tsuzuki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effi ciency of botanic products on insects might vary with UV radiation, temperature, and solvent used, or with the concentration of the extract (Moreira et al, 2007). The genetics of the plant, the extraction time of the compounds (Sidhu et al, 2004), leaf areas, organic compounds of leaves, density of leaf trichomes (Leite et al, 2007), and the part of the plant used for producing the extracts further infl uence the activity of some compounds against insects (Siskos et al, 2007). In addition this product is more effi cient in the fi eld, since it activates substances of the secondary metabolism of the plants and thus improving resistance (Tsuzuki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Standl. (Peronti & Souza-Silva 2002), Sechium edule Swartz (Neupane et al 2006), Cucumis sativus L. (Steenis & El-Khawass 1995), Cucumis melo L. (Kingler et al 1998) and Abelmoschus esculentus (L.) Moench (Leite et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Okra ( Abelmoschus esculentus Moench) is an economically important vegetable crop grown worldwide and is widely consumed in West Africa. In Cameroon, the cotton aphid ( Aphis gossypii Glover) is one of the dominant pests of okra (Leite et al ., ; Shannag et al ., ) and has evolved resistance to pesticides, particularly on cotton plant (Brévault et al ., ). An annual survey conducted by the International Institute of Tropical Agriculture (IITA) in Cameroon (2011) found that okra farmers grow many different okra varieties, various ant species attend aphids on okra, and ants of genus Pheidole were the dominant ant species found attending aphids on okra plants in 75% of the surveyed okra farms (IITA annual survey report, 2011).…”
Section: Introductionmentioning
confidence: 99%